'I don't want my parents' respect going down the drain': South Asian, Muslim young women negotiating family and physical activity. Issue 1 (2nd January 2017) - Stride, Annette; Flintoff, Anne
ABSTRACT: Young women's relationship with physical activity has been explored extensively, yet the focus is often upon young women who are White. This paper considers South Asian, Muslim young women's experiences of physical activity and how these are influenced by family. A 'middle ground' feminist approach is used, drawing upon the work of Hill Collins [(2000). Black feminist thought: Knowledge, consciousness, and the politics of empowerment . London: Routledge] and Hamzeh [(2012). Pedagogies of deveiling: Muslim girls and the hijab discourse (critical construction) . Charlotte, NC: Information Age Publishing]. Data were generated with 13 young women using participatory approaches in focus group settings, and individual interviews. This research highlights how the young women's families can both enable and challenge opportunities and involvement in physical activity. The paper discusses how gender and religion intersect with family and wider community to influence experiences in multiple, diverse and fluid ways. The young women's narratives suggest that experiences are not determined solely by these influences; rather, they emerge as active agents negotiating different contextual challenges in their quest to be physically active.